2012
DOI: 10.1371/journal.pone.0052073
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Coxsackievirus A10 and A6 in Hand-Foot-Mouth Disease in China, 2009–2011

Abstract: Coxsackieviruses A10 (CV-A10) and A6 (CV-A6) have been associated with increasingly occurred sporadic hand-foot-mouth disease (HFMD) cases and outbreak events globally. However, our understanding of epidemiological and genetic characteristics of these new agents remains far from complete. This study was to explore the circulation of CV-A10 and CV-A6 in HFMD and their genetic characteristics in China. A hospital based surveillance was performed in three heavily inflicted regions with HFMD from March 2009 to Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 23 publications
4
103
1
Order By: Relevance
“…1 Over the past 5 years, CVA6 has also been implicated in HFMD outbreaks in Finland, France, Spain, India, Taiwan, Japan, Singapore, China, and Boston, Massachusetts. [2][3][4][5][6][7][8][9][10][11] The atypical cutaneous features characterizing the 2011-2012 North American CVA6-associated HFMD outbreak have not been clearly defined.…”
mentioning
confidence: 99%
“…1 Over the past 5 years, CVA6 has also been implicated in HFMD outbreaks in Finland, France, Spain, India, Taiwan, Japan, Singapore, China, and Boston, Massachusetts. [2][3][4][5][6][7][8][9][10][11] The atypical cutaneous features characterizing the 2011-2012 North American CVA6-associated HFMD outbreak have not been clearly defined.…”
mentioning
confidence: 99%
“…Currently, only two full-length genomes of CV-A10 have been reported (Oberste et al, 2004;Hu et al, 2011), probably because of the regional nature of its distribution or because it is underemphasized (Hu et al, 2011;Lu et al, 2012;He et al, 2013). Thus, there is very little information about the genetics and evolution of CV-A10.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, outbreaks or sporadic cases may also be caused by other human enteroviruses, such as CV-A10. In recent years, CV-A10-related HFMD has been associated with increasingly common but sporadic cases of HFMD, and by global outbreak events (Blomqvist et al, 2010;Wu et al, 2010;Yu and Song, 2010;Davia et al, 2011;Lu et al, 2012;Mirand et al, 2012;He et al, 2013). All of these studies strongly demonstrated that CV-A10 infections are an important cause of HFMD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These viruses contribute to HA and classic or atypical HFMD outbreaks and they can cause severe disease with neurological complications [17][18][19][20][21]. Based on global molecular epidemiology surveillance, EV71, CVA16, CVA6 and CVA10 are the most prevalent pathogens of HFMD in children [1,3,[17][18][19][20][21].…”
mentioning
confidence: 99%